2020
DOI: 10.3389/fpsyt.2020.00282
|View full text |Cite
|
Sign up to set email alerts
|

Is Barthel Index Suitable for Assessing Activities of Daily Living in Patients With Dementia?

Abstract: Objectives: To evaluate application of the Barthel Index (BI) in assessing basic activities of daily living (ADL) of patients with dementia using Rasch analysis. Design: A multi-country cross-sectional study. Setting and Participants: Nineteen long-term care facilities located in China, Japan, South Korea, and Thailand. A total of 644 patients with dementia were included. Methods: Unidimensionality, global and item fit, local dependence, person-item targeting, threshold disordering, and differential item funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 58 publications
3
30
0
2
Order By: Relevance
“…Because the MMSE and MoCA were scored polytomously, the partial credit model was selected for Rasch analysis (Linacre, 2012). A value of zero was allocated to the mean of item difficulty and the mean person location should approximate zero for a well‐targeted tool (Yi et al., 2020). ICC and diagnostic function were analyzed using SPSS version 19.0 (IBM Corp, Armonk, NY, USA).…”
Section: The Studymentioning
confidence: 99%
“…Because the MMSE and MoCA were scored polytomously, the partial credit model was selected for Rasch analysis (Linacre, 2012). A value of zero was allocated to the mean of item difficulty and the mean person location should approximate zero for a well‐targeted tool (Yi et al., 2020). ICC and diagnostic function were analyzed using SPSS version 19.0 (IBM Corp, Armonk, NY, USA).…”
Section: The Studymentioning
confidence: 99%
“…Despite the increasing evidence acknowledging the bene cial effect of exercise on ADL performance, results are still broadly heterogeneous and of low quality (14,44,57). The dose-dependent relationship remains unclear and, although the BI has been used globally (58), empirical evidence regarding its validity for assessing individuals with major NCD is still scarce (59). Even though our previous research demonstrated the bene cial effect of MT intervention in ADL functionality in older adults with major NCD…”
Section: Discussionmentioning
confidence: 95%
“…While Yi et al recommend assessments using the Barthel Test, they also recommended that the assessment tool be tested using the intended target group prior to introducing it into practice. Their study shows the Barthel Test to be unsuitable for use in patients with dementia, in whom the results of independence tests are almost always unreliable and do not correspond with reality [ 33 ].…”
Section: Discussionmentioning
confidence: 99%